Visual and Proprioceptive Influences on Tactile Spatial Processing in Adults with Autism Spectrum Disorders. Issue 12 (11th September 2019) - Hense, Marlene; Badde, Stephanie; Köhne, Svenja; Dziobek, Isabel; Röder, Brigitte
Abstract : Children with autism spectrum disorders (ASDs) often exhibit altered representations of the external world. Consistently, when localizing touch, children with ASDs were less influenced than their peers by changes of the stimulated limb's location in external space [Wada et al., Scientific Reports 2015, 4(1), 5985]. However, given the protracted development of an external‐spatial dominance in tactile processing in typically developing children, this difference might reflect a developmental delay rather than a set suppression of external space in ASDs. Here, adults with ASDs and matched control‐participants completed (a) the tactile temporal order judgment (TOJ) task previously used to test external‐spatial representation of touch in children with ASDs and (b) a tactile‐visual cross‐modal congruency (CC) task which assesses benefits of task‐irrelevant visual stimuli on tactile localization in external space. In both experiments, participants localized tactile stimuli to the fingers of each hand, while holding their hands either crossed or uncrossed. Performance differences between hand postures reflect the influence of external‐spatial codes. In both groups, tactile TOJ‐performance markedly decreased when participants crossed their hands and CC‐effects were especially large if the visual stimulus was presented at the same side of external space as the task‐relevant touch. The absence of group differences was statistically confirmed using Bayesian statistical modeling: adults with ASDs weighted external‐spatial codes comparable to typically developed adults during tactile and visual‐tactile spatio‐temporal tasks. Thus, atypicalities in the spatial coding of touch for children with ASDs appear to reflect a developmental delay rather than a stable characteristic of ASD. Autism Res 2019, 12: 1745–1757 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: A touched limb's location can be described twofold, with respect to the body (right hand) or the external world (right side). Children and adolescents with autism spectrum disorder (ASD) reportedly rely less than their peers on the external world. Here, adults with and without ASDs completed two tactile localization tasks. Both groups relied to the same degree on external world locations. This opens the possibility that the tendency to relate touch to the external world is typical in individuals with ASDs but emerges with a delay.